Relevansi Konstitusi dalam Menjamin dan Menegakkan HAM (Hak Asasi Manusia) di Indonesia - Iqbal Aji Saputra; Salsabila Aprilia (Universitas Katolik Widya Karya Malang, 2023)
The Constitution is the highest law in Indonesia and is the foundation for the protection and upholding of Human Rights (HAM). The Indonesian constitution regulates human rights in various articles, such as freedom of expression, the right to education, the right to health, the right to work, and so on. However, there are still many cases of human rights violations that occur in Indonesia. Therefore, it is important to evaluate the relevance of the constitution in guaranteeing and upholding human rights in Indonesia. This study uses a qualitative approach with content analysis techniques for constitutional documents and laws related to human rights as well as literature studies. The results of the research show that the Indonesian constitution provides a strong basis for protecting and upholding human rights. However, in practice there are still obstacles such as a weak law enforcement system, corruption, and policies that are not progressive in promoting human rights. Therefore, efforts are needed to increase public understanding and awareness of human rights and strengthen institutions that play a role in upholding law and human rights in Indonesia. In addition, there is a need for efforts to adopt progressive policies in promoting human rights and guaranteeing their protection in accordance with the constitution. Thus, it is hoped that the constitution can become an effective instrument in guaranteeing and upholding human rights in Indonesia.